Finite element analysis of go-kart chassis / Mohamad Azri Haziq Mohd Jafri ... [et al.] - Mohd Jafri, Mohamad Azri Haziq; Marwan, Shahrul Hisyam; Mohd Lazim, Muhammad Khairudin; Mohd Anuar, Nurul Damia (2019)
This paper aims to model, simulate and perform the static analysis of a go-kart chassis consisting of circular beams. Modelling, simulations and analysis are performed using modelling software i.e. SolidWorks for Go Kart Challenges 2017 (GKC-17). The maximum stress and displacement is determined by performing static analysis. The result of maximum stress is compared to maximum yield strength of maximum stress whether the maximum stress is exceeding the maximum yield strength or not. It can also show the displacement where it shows the deformation of the chassis part when the load applied to the chassis